Origin of relaxor behavior in 0.78(Na0.5Bi0.5)TiO3-0.2SrTiO3-0.02BaTiO3 ceramic: An electrical modulus study. (October 2018) - Praharaj, S.; Subramanian, V.; Kang, S.-J.L.; Rout, D.
Graphical abstract: Highlights: Implementation of IS technique to study thermal evolution of polar nano regions. Indirect evidence of the existence of polar nano regions well above TB and below T f . Visualization of relaxation dynamics of PNRs on cooling by a schematic diagram. Abstract: The relaxation dynamics of the polar nano-regions (PNRs) in the 0.78Na0.5 Bi0.5 TiO3 -0.2SrTiO3 -0.02BaTiO3 lead free ternary system over a wide temperature range (50–650 °C) is investigated using complex electric modulus formalism. The modulus spectra are analyzed across three characteristic temperatures TB, Tm, and Tf with a special focus on the evolution of dynamics of PNRs. Portraying high capacitance of shoulder response as compared to the bulk response in M"( f ) spectra shows indirectly the presence of highly polarisable entities that persist even above TB and below Tf . The activation energies extracted from an Arrhenius fit to the relaxation time of both bulk and shoulder response signify different relaxation mechanisms. Further, the value of the stretched exponent β and the scaling behavior study of the M"( f ) spectra envisage temperature sensitive dipolar relaxation.